ENERGY AND AGRICULTURAL POLICIES OVER THE TRANSBOUNDARY SURFACE WATER RESOURCES - Mehmet Kucukmehmetoglu (European Regional Science Association (ERSA), 2011)
Allocation of transboundary water resources involves not only the competing parties divided by geographic and administrative boundaries (regional, national and local boundaries) but also takes place among various sectors (agricultural, urban, and industrial etc.) and various time periods (monthly, seasonal, annual). This study uses the Inter-Temporal Euphrates and Tigris River Basin Model (ITETRBM), which is a linear programming model maximizing net economic benefit derived from energy generation, agricultural and urban uses after conveyance costs. While optimally allocating water resources, The ITETRBM enables to pursue various sensitivity analyses in order to measure the impacts of annual changes in the energy and water demand over the countries (Turkey, Syria, Iraq) and sectors (agriculture, urban) in the Euphrates and Tigris River Basin (ETRB). The results present that i) energy and agriculture are two different sectors potentially compete each other, and ii) that competition opens a wide spectrum of water and energy policies in the basin among all countries. The spectrum of policies may cover the issues of a) time preferences of energy generation via hydroelectric power plants especially in the relatively cold upstream countries and b) utilization of alternative energy recourses and their preferential uses in upstream and downstream countries. While managing agriculture and energy sectors, an integrative approach potentially brings a superior allocation solution that provides higher welfare to the basin countries.
Keywords: 330